Molecular docking studies and biological evaluation of chalcone based pyrazolines as tyrosinase inhibitors and potential anticancer agents. Issue 57 (25th June 2015) - Qin, Hua-Li; Shang, Zhen-Peng; Jantan, Ibrahim; Tan, Oya Unsal; Hussain, Muhammad Ajaz; Sher, Muhammad; Bukhari, Syed Nasir Abbas
<x xml:space="preserve">Abstract</x> A series of synthetic chalcones and pyrazoline derivatives showed antityrosinase, anticancer and considerable tubulin polymerization activity.